Frontalis Sling Surgery With IBCN-Ritleng Probe: A New Technique With a 20-Gauge Catheter. Issue 5 (July 2016) - Griffa, Alessandro; Rossi, Vincent; Jacobbi, Marco; Perottino, Flavio
Abstract : Introduction: Frontalis sling surgery is the reference procedure for severe ptosis due to poor Levator function. Autologous or synthetic materials are used for lifting the upper eyelid. Objective: To describe a new technique of passage of a silicon wire through a 20-gauge intravenous catheter and to explore literature. Methods: A 83-year-old male patient with simple, severe ptosis with previous levator resection surgery (7 month before) had frontalis sling with a silicone IBCN wire placed under local anesthesia with a closed technique. It consisted in realization of 3 punctiform incisions upper the eyebrow, through which a 20G intravenous catheter was inserted and droven to the free border of the upper eyelid. The polypropylene part of the IBCN probe silicone tube, IBCN set, was interlocked into the needle tip, enabling to drag the wire through its tunnel without eyelid dissection. The body of the IBCN probe was consequently placed on the free edge of the eyelid, whereas its 2 ends were tied under the middle upper eyebrow incision, enabling to adjust tension of the probe according to the severity of ptosis. The node was kept subcutaneously, allowing correction "on demand" of wire tension in the future by the surgeon. Results: No infections, exposures, or granuloma formations were seen in our patient at 2 months, whereas visual field was improved and the patient fully satisfied. Discussion: Small punctiform incisions and limited skin dissection offer a significant advantage, as well as the materials that are easy to access and cheap, in the frontalis sling surgery. Conclusion: The authors added to frontalis sling surgery a simple and cost-effective alternative technique of passage of a subcutaneous probe, with an IBCN wire whose dimensions fit perfectly a 20-gauge intravenous catheter and allowing later correction "on demand" of the ptosis.